High-Resolution and High-Speed Integrated CMOS AD Converters for Low-Power Applications - Li, Weitao; Li, Fule.; Wang, Zhihua; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is a step-by-step tutorial on how to design a low-power, high-resolution (not less than 12 bit), and high-speed (not less than 200 MSps) integrated CMOS analog-to-digital (AD) converter, to respond to the challenge from the rapid growth of IoT. The discussion includes design techniques on both the system level and the circuit block level. In the architecture level, the power-efficient pipelined AD converter, the hybrid AD converter and the time-interleaved AD converter are described. In the circuit block level, the reference voltage buffer, the opamp, the comparator, and the calibration are presented. Readers designing low-power and high-performance AD converters won't want to miss this invaluable reference. Provides an in-depth introduction to the newest design techniques for the power-efficient, high-resolution (not less than 12 bit), and high-speed (not less than 200 MSps) AD converter; Presents three types of power-efficient architectures of the high-resolution and high-speed AD converter; Discusses the relevant circuit blocks (i.e., the reference voltage buffer, the opamp, and the comparator) in two aspects, relaxing the requirements and improving the performance.
Introduction -- ADC Architecture -- Reference Voltage Buffer -- Amplification -- Comparator -- Calibration -- Design Case -- Contributions and Future Directions.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation